A STRATEGIC FOCUS ON ADOPTION OF MOBILE TAXI APPLICATION- A MOVE TOWARDS DIGITAL INDIA - Dr. Anurag Kumar, Dr. Ajay Singh, Dr. Rahul Gupta (International Journal of Advanced Science and Technology, 2020)
The digital landscape is emerging and evolving rapidly, with countless innovations emerging nowadays. In the past decades, transportation facilities underwent significant changes. Among different transportation modes available in market the cabs services has emerged an important transportation mode in the major Indian cities. The taxi-aggregator companies are growing significantly with the support of technology. It is one of the major moves towards digital India. Nowadays, Indian citizens are using mobile applications to book cabs as per their convenient time and location in various Indian metropolitan cities. This study is aimed to measure and evaluate the factors which are influencing towards the digital adoption of m-taxi services among Indian citizens. An extended Technology acceptance model (TAM) is used as the model for prediction. A structured questionnaire was used and data was collected from the 250 respondents who are Indian citizens and belong to National Capital Region of India. Collected data was analyzed through structural equation modelling and the results identified that 65% of citizen’s has attitude of behavioural intention towards the digital adoption of mobile taxi application (m-taxi apps). Several practical recommendations based on the results were also suggested that can be used as input for policy makers and company management to consider in their efforts to improve the services and behavioural pattern of Indian citizens towards the adoption of m-taxi apps.